Cyber Crime and the Courts—Investigating and Supervising the Information Age Offender. - Newville, Lanny L. (Federal Probation, 2001)
The author presents a review of trends and the growth of computer crime in the federal courts, examining the impact of “high-tech” defendants/offenders on the system, and proposing methods to enhance effectiveness of investigation and supervision. He advocates instituting training programs and regional computer forensics labs to serve as resources for the Courts to assist in the monitoring and supervision of defendants charged with computer-related crimes. Reprinted by permission of the publisher.